IMPLEMENTATION PROMPTNESS ANALYSIS IN MENINGOCOCCAL MENINGITIS VACCINATION IN UMRAH PILGRIMS IN SURABAYA - Putri Yuliasari; Pujo Suwanto (Universitas Airlangga, 2019)
Background: Umrah pilgrims have a high potential risk of getting infected by Meningococcus Meningitis . Even though meningitis cases had never happened in Indonesia, The vaccination carried out less than 14 days in the Port Health Office Class I of Surabaya (PHO) was still found in December 2018. Purpose: The research aims to analyze the accuracy of Meningococcus Meningitis immunization in the Port Health Office Class I Surabaya (PHO) at Tanjung Perak Port Work Area in December 2018. Methods: The research was carried out in a quantitative descriptive study with a cross-sectional study design. The research samples included all Umrah pilgrims who were vaccinated with Meningococcus Meningitis immunization. The variables consisted of age, time-range of vaccination implementation, gender, and domicile/residence of respondents. The data analysis was carried out using univariate analysis and displayed in the form of a frequency table. Results: This study indicated that almost all pilgrims were vaccinated in more than or equal to 14 days (76%). Meanwhile, the others (24%) were vaccinated at less than 14 days, i.e., at 5-6 days before departure. The majority of pilgrims with a history of vaccinations on less than 14 days of departure were female (56.12%) and lived in Surabaya (55.27%). Conclusion: The majority of the pilgrims in PHO Class I of Surabaya had carried out Meningococcus Meningitis vaccination promptly. However, a small number of pilgrims did not carry out vaccinations under the specified time. Female pilgrims, mostly domiciled in Surabaya, dominated the vaccination on less than 14 days.